PENGARUH BIMBINGAN KELOMPOK TERHADAP KEDISIPLINAN SISWA KELAS IX DI SMP ISLAM INTEGRAL LUQMAN AL-HAKIM - Muhd Riduwan; Rahayu Lestari (LP2M-Institut Agama Islam Abdullah Said Batam, 2023)
This study aims to obtain an overview of the influence of Group Guidance on the Discipline of Class IX Students at SMP Islam Integral Luqman Al-Hakim Batam. This research is a quantitative study that uses samples and populations. The data collection technique in this study used the questionnaire method. The results of the analysis showed that from two variables, namely group guidance and student discipline from the results of the linear regression test, it showed a sig value = 0.000 for the group guidance variable, this means that group guidance has an influence on student discipline. And also Based on the results of the coefficient of determination obtained from R Square there is a value of 21.0% so that it can be known the influence of group guidance on the discipline of class IX students in SMPII luqman Al-Hakim batam by 21.0% and the rest is influenced by other factors.